2022
DOI: 10.3390/genes13091564
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome and Mycobiome Alterations in an In Vivo Model of Alzheimer’s Disease

Abstract: Gut microbiota has emerged as an important key regulator of health and disease status. Indeed, gut microbial dysbiosis has been identified in an increasing number of diseases, including neurodegenerative disorders. Accordingly, microbial alterations have been reported also in Alzheimer’s disease (AD), suggesting possible pathogenetic mechanisms contributing to the development of specific AD hallmarks and exacerbating metabolic alterations and neuroinflammation. The identification of these mechanisms is crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In addition to the intestinal bacteria noted by most researchers, some studies have also found specific alterations in MCI patients in the genus Fungi and a clear correlation with AD biomarkers ( Nagpal et al, 2019 ). More importantly, the different microbiome and fungal biota composition in 3xTg-AD mice is similar to the microbial variation found in humans, and significantly different taxa may contribute to the pathogenic cues of AD being identified ( D’Argenio et al, 2022 ). However, there are some differences in studies regarding oral microbiology.…”
Section: Crosstalk Between the Peripheral And Central Systems And Alt...mentioning
confidence: 96%
“…In addition to the intestinal bacteria noted by most researchers, some studies have also found specific alterations in MCI patients in the genus Fungi and a clear correlation with AD biomarkers ( Nagpal et al, 2019 ). More importantly, the different microbiome and fungal biota composition in 3xTg-AD mice is similar to the microbial variation found in humans, and significantly different taxa may contribute to the pathogenic cues of AD being identified ( D’Argenio et al, 2022 ). However, there are some differences in studies regarding oral microbiology.…”
Section: Crosstalk Between the Peripheral And Central Systems And Alt...mentioning
confidence: 96%
“…Therefore, increased secondary BAs may be associated with Alzheimer’s disease, and the status of the gut microbiome may affect the progression and suppression of Alzheimer’s disease. In addition, the increase in Lactobacillus , which has BSH that deconjugates conjugated-BAs, in feces is related to Alzheimer’s disease [ 120 , 121 ].…”
Section: Microbiota-modified Bas In Neurodegenerative Diseasesmentioning
confidence: 99%
“… D’Argenio et al (2022) investigated the changes in bacterial and fungal composition in the intestines of wild-type (WT) mice and AD (3xTg-AD mice, one of the most widely used AD models). Compared to WT mice, AD mice showed reduced relative abundance of the phyla Firmicutes, Lachnospiraceae-unclassified, Ruminococcaceae-unclassified, and Turicibacter.…”
Section: Biomarkers Of Alzheimer’s Diseasementioning
confidence: 99%
“…Bacteroidetes is a gram-negative bacteria and the lipopolysaccharide in its outer membrane has pro-inflammatory effects and promotes amyloid protein deposition and tau protein-related pathology. In addition, the authors found a decrease in fungal richness in the feces of AD mice, which may be related to metabolic changes in AD ( D’Argenio et al, 2022 ). Liang et al (2023) transplanted Paenalcaligenes hominis isolated from the feces of elderly humans and mice into young mice and found a decline in cognitive function in the mice.…”
Section: Biomarkers Of Alzheimer’s Diseasementioning
confidence: 99%